Analysis of the International Applicability of Singapore’s Electronic Road Pricing (ERP) and its Impact on Mobility: A Socio- Environmental Approach for the City of Medellin (2017)
The purpose of this research project is to investigate and analyze the international applicability of the Electronic Road Pricing or ERP project implemented in Singapore since 1998 in order to reduce vehicle congestion levels in an urban center or city, reduce emissions from gases that impair air quality and maximize productivity at the local level by generating a more standardized transport time. Indeed, the high traffic congestion that has been increasing in recent years in the city of Medellin has been the cause of severe environmental and social problems for the local population. Even more, the increasing vehicular demand at certain times of the day manages to reduce the productivity of an urban and industrial center such as the capital of Antioquia. Given that these local regulations to improve mobility have not generated a definitive solution, this project seeks to analyze the applicability of a new congestion rate system in the city of Medellin based on the case of the Singapore ERP.